The Development of Anti Bribery Management System: A Preliminary Study - Hasnah, Haron; Ishak, Ismail; Daing Nasir, Ibrahim; Mohd Ridzuan, Darun; Kamal Z., Zamli; Aziman, Abdullah; Gui, Anderes (IEEE, 2018)
This paper explain the development of Anti Bribery Management System (ABMS) checklist to measure the state of readiness of an organization in implementing ABMS in its organization. Three instrumentals consisting of ABMS checklist, ABMS Matrix, and ABMS Dashboard were developed based on international references. ABMS has eight dimensions which are (1)Tone of the top, (2)risk assessment, (3)policies and procedures, (4)training and communication, (5)monitoring and auditing, (6)investigation and reports, (7)enforcement and sanction and (8)review and update. Data was collected in September 2017 from 31 middle and top management level of one organization as a preliminary study. The developed checklist was first validated by panel experts in the subject matter. A briefing session was then made to the respondents and they were then requested to answer the final checklist online. Data collected was then analyzed using descriptive statistics to gauge the perception of respondents towards the extent of implementation of ABMS in an organization. The organization was found to score 63.9%. Recommendations were suggested on how to improve the state of readiness of the implementation of ABMS